Pathway to success: exploring students’ perspectives on career aspirations in pharmacy / Mohd Izani Othman ... [et al.] - Othman, Mohd Izani; Mohd Najib, Mohd Nadzri; Sulaiman, Suraya; Abdul Khalid, Mohd Ikhmal Hanif; Zamri, Muhammad Irfan Daniel; Mohd Shakri, Muhammad Shazani; Mohd Izzudin, Muhammad Akmal (Universiti Teknologi MARA, Perlis, 2024)
Embarking on a career in pharmacy is a dynamic and engaging journey, making it imperative to delve deeper into students' viewpoints. This study holds paramount significance as it seeks to unravel the students' perspectives on choosing pharmacy as a career. Understanding these viewpoints becomes pivotal for academic institutions, guiding them to navigate and align seamlessly with the ever-evolving landscape of pharmacy careers. The objectives of this study include to explore students’ attitudes towards pharmacy as their future career aspiration and to determining the relation between students’ academic performance and their attitudes towards pharmacy as their future career aspiration. Using a cross-sectional survey design, data were collected through Google Forms from ninety Diploma in Pharmacy students of Universiti Teknologi MARA Cawangan Pulau Pinang, Kampus Bertam. Employing a convenient sampling, data tabulation and statistical analysis were executed using SPSS. Results from this study indicate that pharmacy students generally express a high level of pride (88.9%) in their field of study and a strong commitment (88.9%) to the values of the pharmacy profession. Additionally, a significant portion sees being a pharmacist as an integral part of their identity (74.5%). A majority agreed that pharmacy is an ideal lifelong career (76.7%) and expressed contentment with their choice to study pharmacy (68.9%). While a notable percentage would still choose pharmacy if given the chance again (53.4%), there is a consensus (81.1%) that a career in pharmacy is desirable. Importantly, the overall score of 4.07 suggests a general agreement with the positive statements about studying pharmacy. In conclusion, this study illuminates the positive inclinations and affirmations that students hold regarding pharmacy as a career choice. The findings not only contribute valuable insights into the attitudes and perspectives of pharmacy students but also underscore a predominantly optimistic outlook on their chosen profession